Dampak pandemi covid 19 terhadap sektor usaha di kalimantan timur - Irwan Gani (Faculty of Economics and Business Mulawarman University, 2021)
The COVID-19 pandemic is currently of global concern. The case is increasing in East Kalimantan. The government issued a Governor's Instruction No. 1/2021 for the Control, Prevention, and Handling of the Covid-19 pandemic in East Kalimantan. This study uses a reference approach supported by secondary data from the Central Statistics Agency 2020, in addition to government web media information, Instagram, and Twitter data from policymakers. This study aims to describe, explain and analyze the impact of a pandemic in the economic business sector. Besides, some descriptive analyzes were carried out by researchers to provide an overview of how poverty increased in number during this pandemic. The results of this research show that the business sectors that have experienced a decline are in the fields of Agriculture, Forestry, Fisheries; Mining and excavation; Processing industry; Procurement of Electricity, Gas; Construction; Wholesale and Retail Trade and Repair of Automobiles and Motorcycles; Transportation and Warehousing; Provision of accommodation and food and drink; Real Estate; Company Services; Mandatory Government Administration, Defense, and Social Security. Meanwhile, several sectors that have survived the blow during the pandemic are the business sector which includes the sector of water supply, information and communication, financial services, education services, health services, and social activities.